Romance interrogative syntax formal and typological dimensions of variation - Bonan, Caterina (Linguistik aktuell ;, 2021)
"This monograph offers an innovative understanding of the mechanisms involved in Romance 'optional' wh-in situ. New supporting evidence in favour of Cable's (2010) Grammar of Q is presented, as well as novel implementations of his original theory. In particular, it is claimed that wh-in situ idioms are characterised not only by language-specific choices between QP-projection and Q-adjunction, and between overt and covert movement of Q, but also in terms of the locus where they check the features relevant to wh-questions: while some languages check both [q] and [focus] in C, others make use of the clause-internal vP-periphery to check [focus]. Thanks to the vast amount of data presented and discussed, along with the predictions and theoretical contributions made, this monograph will be of interest to a wide range of specialists in human language, from typologists to Romance specialists and formal syntacticians, but also to the many experts in languages with overt Q-particles who wonder why Romance specialists have long been so resistant to the implementation of silent Q-particles in their theoretical models"--